2007
DOI: 10.1021/jp073096t
|View full text |Cite
|
Sign up to set email alerts
|

Surface Diffusion of a Zn Adatom on a Zn(001) Surface:  A DFT Study

Abstract: The adsorption and diffusion of a Zn atom on a Zn(001) surface has been investigated theoretically by using first-principles periodic boundary condition calculations to elucidate the mechanism of crystal growth of zinc in a Zn surface. Three surface models, terrace, step, and kink, of the Zn(001) surface were considered as adsorption sites in the present study. The most stable site in the terrace model was the on-top site, where the zinc adatom is bound to only one zinc atom of the surface. The activation barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Such a difference, however, can be explained with the different degree of relaxation of the systems investigated and the different mechanisms of diffusion taken into account, both in favor of the E a,Sn estimate given in the present work. Another indication in this sense comes from the fact that the E a,Sn value obtained is close to the experimental activation energy for the migration of Sn atoms on a Cu(111) surface, equal to about 24.7 kJ mol −1 , and in line with the activation energies for diffusion processes generally reported in the literature …”
Section: Resultssupporting
confidence: 89%
“…Such a difference, however, can be explained with the different degree of relaxation of the systems investigated and the different mechanisms of diffusion taken into account, both in favor of the E a,Sn estimate given in the present work. Another indication in this sense comes from the fact that the E a,Sn value obtained is close to the experimental activation energy for the migration of Sn atoms on a Cu(111) surface, equal to about 24.7 kJ mol −1 , and in line with the activation energies for diffusion processes generally reported in the literature …”
Section: Resultssupporting
confidence: 89%
“…Iokibe et al 985 studied the adsorption and diffusion of Zn on Zn(001) with the PW91 density functional. Kurzweil and Baer 1094 used a novel DFT approach to study the surface plasmon absorption of Au 8 and Au 18 .…”
Section: Solidsmentioning
confidence: 99%
“…Sorkin et al 431 found that B3LYP and M05-2X both give reasonable results for the binding energies of small Zn clusters. Iokibe et al 985 found that the bond length and cohesive energy of the clusters depends on the extent of 4s/4p mixing, in contrast to earlier transition metals where 4s/3d mixing is a key quantity.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Density functional theory (DFT) is utilized in numerous atomic-scale analyses of chemical processes, including solid–liquid interfacial processes. , Adatom surface diffusion and the adsorption of the metal atoms are also analyzed using DFT. While these studies provide a mechanistic understanding of each process with respect to the electronic state, DFT calculations cannot be used to analyze stochastic phenomena, such as shape evolution over much larger areas. A kinetic Monte Carlo (KMC) simulation is a stochastic simulation that expands the analysis scale from the atomic to the mesoscale to model deposition and nucleation.…”
mentioning
confidence: 99%